BEHIND RISK DISCLOSURE: A STUDY OF INFLUENCING FACTORS - Suwandi, Suwandi; Lambyombar, Yustinus; Eka, Andi Primafira Bumandava (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
Risk disclosure in financial reporting remains suboptimal in several large companies in Indonesia, which can hinder stakeholders’ ability to make informed decisions. This study aims to measure the effect of institutional ownership, independent boards of commissioners, and managerial ownership on risk disclosure in food and beverage companies listed on the Indonesian capital market during the 2019–2024 period. Using a causal research design, this study employed purposive sampling, resulting in 16 companies and 96 observational data points. Multiple linear regression analysis was conducted to examine the relationships among variables, supported by classical assumption tests to ensure data validity. The empirical findings indicate that institutional ownership, independent boards of commissioners, and managerial ownership each have a positive and significant effect on risk disclosure. These results demonstrate that companies with stronger governance structures tend to disclose risks more transparently to meet stakeholder expectations. The findings highlight the importance of strengthening governance mechanisms to improve transparency and enhance stakeholder trust. Practically, the study underscores the need for regulators to develop stricter risk disclosure guidelines tailored to the characteristics of the food and beverage industry. Furthermore, companies are encouraged to enhance oversight roles and align their governance practices with improved risk reporting standards to support long-term sustainability.